Desafíos metodológicos para una nueva filosofía de la tecnología: Entrevista a Nicola Liberati - Pontes Bonfiglioli, Cristina (Prometeica - Revista de Filosofía y Ciencias, 2021)
Nicola Liberati, Associate Professor at Shanghai Jiao Tong University (Dept. of Philosophy, School of Humanities), presents us with his unique view of how Philosophy of Technology can move beyond traditional approaches in Philosophy of Technology to solve current problems we see emerging from the use of the latest technologies in contemporaneity.